The relationship between core values and entrepreneurial performance: a study of SMEs in the informal economy of Uganda's central region - Kintu, Ismail (My University, 2017)
The conceptualisation of core values indicate that they are guiding principles in shaping organisational culture. Furthermore, values enhance firm efficiency if they are well integrated in all business processes. Despite the fact that core values motivate employees, SMEs in the informal economies of developing countries do not provide a list of core values to employees. The purpose of this study, therefore; was to establish the commonly practiced core values in Uganda’s informal economy and whether such core values could motivate and reinforce behaviour among employees and at the same time, foster entrepreneurial performance. The study adopted a mixed methods approach. In this case, the sample size for qualitative interviews was twenty-five respondents whereas the sample size for the quantitative survey was three hundred and eighty-six (386) respondents. The interviews were guided by a semi-structured interview guide and revealed that the commonly practiced core values in Uganda’s informal economy are; cleanliness, trust, fairness, responsibility and respect. It was established that core values motivate and reinforce employee behaviour. The quantitative survey was done using a questionnaire with a five- point Likert scale. Hypotheses and mediation tests were carried out by way of structural equation modeling, using AMOS and Sobel’s test respectively. Results from all hypotheses’ tests indicated significant positive relationships between predictor and outcome variables. However, the relationships of; motivation and entrepreneurial performance and legitimacy and entrepreneurial performance were positive, but insignificant. In addition, it was discovered that the reinforcement theory is applicable in Uganda’s informal economy. Based on the results of this research, it is recommended that SMEs should seek to acquire skills on how to fully turn legitimacy and motivation into business advantage and how to use core values as tools for advertising and marketing the business. Finally, the Ministry of Gender, Labour and Social Development, with help from local governments, should design a policy to tempt SMEs to voluntarily engage in community service, especially cleaning up water and drainage channels to improve cleanliness in the communities as well as improving on business legitimacy.
A thesis submitted to the Faculty of Commerce, Law and management, University of Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy in Business Sciences. Johannesburg, November 2017.
Keywords: Small business--Uganda; Entrepreneurship--Uganda; Informal sector (Economics)--Uganda